The Global Impact of Multisystemic Vulnerabilities on Criminal Variety: A Cross-Continental Study in Young Adults - Villanueva, Lidón (Journal of interpersonal violence, 2025)
Previous research has shown a robust association between different childhood and adolescent vulnerabilities and youth offending. However, these investigations have primarily focused on youths from high-income Western countries. Consequently, the generalizability of these findings to better inform global justice policies remains uncertain. This study aimed to address this gap by examining the relationship between individual, familial, and contextual vulnerabilities and criminal versatility during young adulthood, accounting for sociodemographic factors and cross-national differences. Data were derived from a diverse sample of 4,182 young adults (67% female; mean age = 18.96; SD = 0.81) residing in 10 countries across 5 continents who participated in the International Study of Pro/Antisocial Behavior in Young Adults. The Psychosocial and Family Vulnerability Questionnaire and the Adverse Childhood Experiences questionnaire were used to assess social and family adversity, and past-year criminal diversity was measured with the Criminal Variety Index. Results indicate that child maltreatment, substance abuse, and delinquent peers are global risk factors for criminal variety. Moreover, they are independent across males and females and among youths living in countries that are ranked differently on the Human Development Index (HDI). In addition, some childhood vulnerabilities showed different predictive ability across sexes (e.g., school failure), and across countries ranked differently on the HDI (e.g., family dysfunction). These findings suggest that certain childhood factors contribute to criminal behavior through transcultural mechanisms. Moreover, they highlight the importance of developing evidence-based policies that focus on transcultural risk factors to globally prevent criminal behavior.